The Impact of Group Counseling on Psychological Status of Iranian Infertile Women: A Systematic Review - Sanaz Mollazadeh; Nasim Shahrahmani; Masoumeh Sadeghi; Malihe Mahmoudinia; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2024)
Background & aim: Infertility counseling has become a professional method of counseling demanding specialized proficiency and qualification to address this crucial issue. Counseling can be done as individual, couples, or group counseling. This study intended to systematically review the published articles on the impact of group counseling on the psychological status of infertile women.Methods: This systematic review was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) from conception to April 14, 2023.  English databases including Web of Science, Cochrane Library, Medline (via PubMed), Scopus, and ProQuest, as well as Persian databases of Magiran and SID, were searched independently by two researchers. Review Manager (Rev Man) version 5.3 and the Cochrane Risk of Bias (ROB) tool for randomized trials and JBI for clinical trials were used to assess the quality of articles.Results: Out of the 1,264 retrieved articles from related databases, 1034 articles were screened. Ten clinical trials including 694 infertile women, were included in this systematic review. The results show that group counseling is one of the most effective methods for improving psychological status of infertile women.Conclusion: The results of this study indicated that group counseling using different approaches is effective in improving the psychological status of infertile women. It is suggested to perform clinical trials with robust methodology, a larger sample size, and long-term follow-up to gain more generalizable results.